Re: Lung and cardiac ultrasound for hemodynamic monitoring of patients with severe pre‐eclampsia. J. Ambrozic, G. Brzan Simenc, K. Prokselj, N. Tulz, M. Cvijic and M. Lucovnik. Ultrasound Obstet Gynecol 2017; 49: 104–109. (January 2017) - Zieleskiewicz, L.; Leone, M.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 49: 104–109